2009
DOI: 10.1056/nejmoa0810635
|View full text |Cite
|
Sign up to set email alerts
|

Diacetylmorphine versus Methadone for the Treatment of Opioid Addiction

Abstract: Injectable diacetylmorphine was more effective than oral methadone. Because of a risk of overdoses and seizures, diacetylmorphine maintenance therapy should be delivered in settings where prompt medical intervention is available. (ClinicalTrials.gov number, NCT00175357.)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
250
1
6

Year Published

2010
2010
2020
2020

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 322 publications
(269 citation statements)
references
References 21 publications
12
250
1
6
Order By: Relevance
“…Recently, it has been suggested that more difficult-to-treat patients may do better in maintenance treatment using diamorphine (heroin). Clinical studies in Switzerland (Perneger et al, 1998;Rehm et al, 2001), the Netherlands (Blanken et al, 2005;van den Brink et al, 2003), Spain (March et al, 2006), Germany (Haasen et al, 2007;Verthein et al, 2008) and Canada (Oviedo-Joekes et al, 2009) have found heroin-assisted treatment (HAT) to be more effective than MMT in the treatment of methadone nonresponders. However, these studies have not analyzed the effect of HAT compared to MMT on BZD use.…”
Section: An Official Document Of the Us Department Of Health And Humentioning
confidence: 99%
“…Recently, it has been suggested that more difficult-to-treat patients may do better in maintenance treatment using diamorphine (heroin). Clinical studies in Switzerland (Perneger et al, 1998;Rehm et al, 2001), the Netherlands (Blanken et al, 2005;van den Brink et al, 2003), Spain (March et al, 2006), Germany (Haasen et al, 2007;Verthein et al, 2008) and Canada (Oviedo-Joekes et al, 2009) have found heroin-assisted treatment (HAT) to be more effective than MMT in the treatment of methadone nonresponders. However, these studies have not analyzed the effect of HAT compared to MMT on BZD use.…”
Section: An Official Document Of the Us Department Of Health And Humentioning
confidence: 99%
“…Lastly, duration on OAT or "retention" in treatment is highly correlated with better health outcomes in opioid dependent patients (11,(20)(21)(22)(23). The longer patients continued in a treatment program, maintain contact with a health care team and provide evidence of maintaining their will to remain abstinent, the better their treatment outcomes.…”
Section: Literature Review: Item Generation Resultsmentioning
confidence: 99%
“…A number of research trials have compared giving treatment-resistant addicts daily heroin (usually self-administered within a clinical setting) with oral and injectable methadone (Hartnoll et al, 1980;Perneger et al, 1998;van den Brink et al, 2003;Haasen et al, 2007;Oviedo-Joekes et al, 2009). The trials indicate that provision of heroin produces benefits for users and for the wider society: improvements in mental and physical health and a decrease in street crime in the patients provided with heroin, compared with those provided with oral or injectable methadone.…”
Section: IImentioning
confidence: 99%